Bingo - Brown, Rita Mae 1944- (A Bantam trade paperback : novel, 1999)
Newspaper editor Nickel Smith is crambling to save the local paper from corporate extinction, even as she is engaged in an affair that would shock the town as much as it amazes Nickel herself.